2016
DOI: 10.1007/s10802-016-0165-5
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Mind-Mindedness Provides a Buffer for Pre-Adolescents at Risk for Disruptive Behavior

Abstract: Maternal mind-mindedness, defined as the propensity to view one’s child as an agent with independent thoughts and feelings, mitigates the impact of low maternal education on conduct problems in young children (Meins et al. 2013), but has been little studied beyond the preschool years. Addressing this gap, we applied a multi-measure and multi-informant approach to assess family adversity and disruptive behavior at age 12 for a socially diverse sample of 116 children for whom ratings of disruptive behavior at ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 54 publications
2
24
0
Order By: Relevance
“…In the recent years, maternal mentalization has been linked with various positive aspects of the parent-child relationship, most notably maternal sensitivity (e.g., Ensink et al, 2016;Koren-Karie et al, 2002;Meins et al, 2001;Zeegers et al, 2017) and secure attachment (e.g., Kelly et al, 2005;Oppenheim et al, 2012;Laranjo et al, 2008;Zeegers et al, 2017). Furthermore, maternal mentalization, as measured using online and offline MM scales, has been associated with children's cognitive and socioemotional development (e.g., Bernier et al, 2017;Hughes et al, 2016;Meins et al, 2013). The aim of the present study was to further understand these early processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the recent years, maternal mentalization has been linked with various positive aspects of the parent-child relationship, most notably maternal sensitivity (e.g., Ensink et al, 2016;Koren-Karie et al, 2002;Meins et al, 2001;Zeegers et al, 2017) and secure attachment (e.g., Kelly et al, 2005;Oppenheim et al, 2012;Laranjo et al, 2008;Zeegers et al, 2017). Furthermore, maternal mentalization, as measured using online and offline MM scales, has been associated with children's cognitive and socioemotional development (e.g., Bernier et al, 2017;Hughes et al, 2016;Meins et al, 2013). The aim of the present study was to further understand these early processes.…”
Section: Discussionmentioning
confidence: 99%
“…Online maternal mentalization during infancy has been positively associated with children's language acquisition in toddlerhood (Laranjo & Bernier, ), executive functioning (Bernier, Carlson, Deschênes, & Matte‐Gagné, ), school readiness in preschool (Bernier et al., ), and theory of mind development (e.g., Devine & Hughes, ; Kirk et al., ; Meins et al., ). Furthermore, high prenatal (offline) as well as postnatal (online) maternal mentalization predicts lower levels of internalizing and externalizing behaviors in toddlerhood (Meins, Centifanti, Fernyhough, & Fishburn, ; Smaling, Huijbregts, van der Heijden, van Goozen, & Swaab, ), suggesting that maternal mentalization can buffer against the development of conduct problems (e.g., Hughes, Aldercotte, & Foley, ). Thus, understanding the processes by which online maternal mentalization relates to other positive aspects of mother–infant and mother–father–infant interactions, namely maternal sensitivity and family triadic interaction (e.g., Feldman & Masalha, ; McHale & Rasmussen, ), can help illuminate important precursor of early development.…”
Section: Maternal Mentalization and Behaviors During Observed Dyadic mentioning
confidence: 99%
“…The authors argue that mind-mindedness may act as a protective factor in children's social and behavioural adjustment. A recent study has found a comparable effect of maternal mind-mindedness on social adjustment in 12 year old children (Hughes, Aldercotte, & Foley, 2017). However, to the best of our knowledge, no study has measured the effect of early MST on behavioural adjustment beyond the early years.…”
mentioning
confidence: 88%
“…Our third aim was to test the longitudinal relation between early maternal MST and reported child adjustment at age 10. Previous research has addressed this association within the preschool years (Meins, et al, 2013) and cross-sectionally at 12 years old (Hughes et al, 2017) but not examined the longitudinal relationships between these ages. For the current study we hypothesized that early maternal MST at age 3 to 4 would act as a protective factor against externalising and internalising behaviour at age 10.…”
mentioning
confidence: 99%
“…Research supports the facilitative influence of "appropriate" maternal mind-mindedness on a range of child developmental domains, including attachment security , executive function and self-regulation Bernier et al, 2017) and social cognition (Laranjo, Bernier, Meins, & Carlson, 2014;. The few studies that have investigated the relationship between maternal mind-mindedness and child behaviour problems (Easterbrooks et al, 2017;Hughes, Aldercotte, & Foley, 2016) suggest that these associations are complex and may be influenced by contextual factors . For example, maternal mind-mindedness has been demonstrated to predict lower internalising and externalising problems only amongst pre-schoolers from low socio-economic status families .…”
Section: Prenatal Maternal Stress: Postnatal Mediators and Moderators?mentioning
confidence: 98%